Bacteriophage RNA polymerases: catalysts for mRNA vaccines and therapeutics - Nair, Adithya; Kis, Zoltán (Frontiers in Molecular Biosciences, 2024)
Decades of research on bacteriophage-derived RNA polymerases (RNAPs) were vital for synthesizing mRNA using the in vitro transcription (IVT) reaction for vaccines during the COVID-19 pandemic. The future success of mRNA-based products relies on the efficiency of its manufacturing process. mRNA manufacturing is a platform technology that complements the quality by design (QbD) paradigm. We applied the QbD framework in combination with key mechanistic insights on RNAP to assess the impact of IVT-associated critical process parameters (CPPs) and critical material attributes (CMAs) on the critical quality attributes (CQAs) of the mRNA drug substance and on manufacturing key performance indicators (KPIs). We also summarize the structure-function relationship of T7 RNAP and its engineered mutants aimed at enhancing the critical production of low-immunogenic mRNA therapeutics. Alternatives to the current set of standard RNAPs in large-scale IVTs are also discussed based on a phylogenetic background. Finally, the review dives into the economic implications of improving mRNA manufacturing based on the main enzyme, T7 RNAP, used to synthesize the mRNA drug substance. The review concludes by mapping the relationship between various CMAs and CPPs with different phases of the IVT reaction from a QbD perspective.